180k views
1 vote
Solve the simultaneous equation y-2x+1=0 and 4x^2+3y^2-2xy=7

1 Answer

1 vote

The first equation is
y-2x+1=0


y=2x-1 (Equation 1)

The second equation is
4x^(2)+3y^(2)-2xy=7 (Equation 2)

Putting the value of x from equation 1 in equation 2.

we get,


4x^(2)+3(2x-1)^(2)-2x(2x-1)=7


4x^(2)+3(4x^(2)+1-4x)-4x^(2)+2x=7

by simplifying the given equation,


12x^(2)-10x-4=0


6x^(2)-5x-2=0

Using discriminant formula,


D=b^(2)-4ac


D=25-4 * 6 * -2 = 73

Now the formula for solution 'x' of quadratic equation is given by:


x=(-b+√(D))/(2a) and x=(-b-√(D))/(2a)


x=(5+√(73))/(12) and x=(5-√(73))/(12)

Hence, these are the required solutions.

User Genusatplay
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.